THU0053 Anti-TNF Treatment Results in a Lower Activation State and Prothrombotic Profile of Platelets from Patients with Rheumatoid Arthritis. (23rd January 2014) - Baldini, M.; Maugeri, N.; Rovere-Querini, P.; Baldissera, E.; Peretti, G.; Sabbadini, M. G.; Manfredi, A. A.
Abstract : Background: Cardiovascular disease is the major cause of mortality in patients with rheumatoid arthritis (RA) and it is not fully explained by traditional risk factors. Some evidence exists that RA treatment, in particular with anti-TNF agents, may reduce the disease-related cardiovascular risk. Platelet activation and the presence of platelet-leukocyte heterotypic aggregates characterize acute coronary syndromes [1, 2 ] and other conditions associated with increased thrombotic risk, including RA [2, 3 ]. TNF-alpha regulates the expression of Tissue Factor (TF), the initiator signal of the extrinsic pathway of the coagulation cascade, by neutrophils [4 ]. Platelets express functional TF upon activation [5 ]. Objectives: To analyze the effect of TNF-alpha pharmacological blockade on platelet and leukocytes activation and TF expression. Methods: Flow cytometry markers of platelet and leukocyte activation and the fraction of heterotypic aggregates were assessed in patients with RA (n = 42), osteoarthritis (OA, n = 12), chronic stable angina (CSA, n = 37) and age- and sex-matched healthy controls (HC, n = 70). 11 RA patients were untreated, 19 on DMARDs and 12 on anti-TNF therapy, i.e. etanercept (n = 8) or adalimumab (n = 4). Results: Platelets from RA patients were activated compared to control groups, as revealed by the significant increase in P-selectin expression and by the higher fraction of circulating heterotypic aggregates. Circulating neutrophils were also significantly activated in RA. The expression of TF by circulating platelets and leukocytes was significantly higher in RA patients compared to control groups. Among RA patients, platelet P-selectin and TF expression were significantly higher in untreated patients, while patients in the anti-TNF group showed a significantly lower expression of platelet and neutrophil activation markers. Moreover, TNF treatment resulted in a significant reduction in platelet TF expression. DMARDs alone were poorly effective in reversing the activated phenotype of platelets from RA patients. Conclusions: RA patients exhibit a significant platelet and leukocyte activation, resulting in their reciprocal physical interaction and in TF expression, which may contribute to the increased cardiovascular risk in these patients. Anti-TNF treatment results in a significant reduction in platelet activation and TF expression, suggesting a role of TNF-alpha pathway in the prothrombotic risk of RA patients. References: Maugeri N et al. Early and transient release of leukocyte pentraxin 3 during acute myocardial infarction. J Immunol 2011. Maugeri N et al. An intense and short-lasting burst of neutrophil activation differentiates early acute myocardial infarction from systemic inflammatory syndromes. PLoS One 2012 Joseph JE et al. Increased circulating platelet-leucocyte complexes and platelet activation in patients with antiphospholipid syndrome, systemic lupus erythematosus and rheumatoid arthritis. Br J Haematol 2001. Kambas K et al. C5a and TNF-alpha up-regulate the expression of tissue factor in intra-alveolar neutrophils of patients with the acute respiratory distress syndrome. J Immunol 2008. Panes O et al. Human platelets synthesize and express functional tissue factor. Blood 2007. Disclosure of Interest: None Declared